Urgensi konseling pranikah calon pasangan suami istri di Pamekasan Madura - Amelia, Fuji Nur Rizqi (Maliki Interdisciplinary Journal, 2024)
Ther has been a lot of premarital counselling with several approaches and techniques in Indonesia, but premarital counselling based on local culture and wisdom has not been seen until now. Many marriages are found to be inharmonious due to a lack of Larangan Tokol who are located on Madura Island need to know before entering the life of husband and wife, apart from that, so that prospective husband and wife partners can truly ensure mental readiness in facing married life later because of marriage. Not only does it require physical readiness, this study is a qualitative study in terms of the type of research usedie case study method collection of information technique used in this research is observations using literature study notes from various previous journal related to married life in the village of Larangan Tokol to find out what things are needed to build a harmonious marriage. The objek of this research is the failure of a husband and wife’s marriage with the problem of lack of knowledge about what things must be prepared for marriage. Things that become provisions for marital life include: reproductive health of prospective married couples, pregnancy and 4T, contraceptive methods, sexually transmitted infections (STIs), stunting and parenting 1000 HPK.